Fifty Years of Justice : A History of the U.S. District Court for the Middle District of Florida - Denham, James M. (Book collections on Project MUSE., 2015)
This book looks at the U.S. Middle District Court of Florida, which represents about 1/2 of Florida's population and is one of the busiest courts in the state, interpreting and applying Supreme Court decisions in cases such as the Terry Schaivo "right to die" case.